Database and Molecular Visualisation for Learning Media of Teaching Computational Chemistry/Pharmacy in Undergraduate Level - Nirwan Syarif; Supriatini Supriatini (AL-ISHLAH: Jurnal Pendidikan, 2023)
Teaching chemistry in the information technology era has made it easy to understand topics related to the structure and properties of a molecule. One of the courses that intensively utilises information technology as a learning media is computational chemistry. This study measured student-learning outcomes during computational courses using molecular visualization software and databases.  The instruments of this research are the results/answers of final exams and the assignments of the students in the semesters of 2018/2019 and 2019/2020  in the chemistry and pharmacy departments. A hundred students enrolled in these courses per year. The study was conducted for two years. The score results of six assignments for practical and four essay questions tests were analyzed. Students were asked to visualize molecules using the requested application in practical test. The assessment shows that project scores with the topic of using databases and visualization, a 'good' score profile of the results the two years. The student has ‘good’ score on small molecule database and visualization. The students mastered the Avogadro application more than VMD. Students generally understand to get data (computer files) from the database and then the visual constructions requested by the questions.